Development of Spectrophotometry Method For Iodide Determination Based on I2-Starch Complex Formation with Hypochlorite as oxidator - Qurrata Ayun; Hermin Sulistyarti; Atikah Atikah (Chemistry Department, The University of Brawijaya, 2015)
Iodine is one of the most important elements for human body. Both, the overage and the deficiency supply of iodine give negative impact for human health. In this research, a simple and inexpensive spectrophotometric method is developed is based on starch-iodine complex formation, where iodide was oxidized with hypochlorite to form iodine, which then reacted with starch to form a blue starch-iodine complex. In this research, the common analytical parameters were optimized regarding to sensitivity and selectivity. It was noted that maximum wavelength for starch-iodine complex was 618 nm, optimum time for complex formation and oxidation was 15 minutes, and optimum hypochlorite concentration was 6 ppm. Under the obtained optimum conditions, the proposed method showed linearity from 0-20 ppm iodide (r2 = 0.994), with limit detection of 0.20 ppm. Determination of iodide with this method was unaffected by Cl-, and Br-; but SCN- affected the measurement of iodide at concentration of 1 ppm. Application to synthetic and urinary samples showed that the proposed method has good agreement with the standard spectrophotometry (leuco crystal violet method), and can be used as an alternative method for iodide measurement.